Tingkat Partisipasi Politik Dalam Pemilihan Gubernur Jawa Tegah di Kabupaten Blora Tahun 2018 - Ghausthauf Anas Mahendra; Bambang Eka Cahya Widodo (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2019)
Community political participation in the election of governors and deputy governors is a form of democratic process in a democratic country. The election of the governor and deputy governor in Java was followed by two governor and deputy governor candidates. Candidates for number one are Ganjar Pranowo and Taj Yasin. Then for the second serial number candidates are Sudirman Said and Ida Fauziah. The researcher used qualitative research methods. Data sources presented as authors are primary data and secondary data. Primary data obtained from observations or interviews conducted by the author immediately jumped into the field. Then the following data is secondary data. Secondary data obtained by researchers from the documentation and voter data obtained from Blora Regency KPU and Central Java Provincial Election Commission office. In collecting data, the author uses interview and observation methods. Data analysis is done in several ways, namely by combining data, reducing data, and then drawing conclusions.The results of the study indicate that: the factors that influence participation are differences in the interests of candidates. Then the people did not really know the governor and deputy governor candidates. The next factor is that the social structure of the community at the village level also opposes people's interest in coming to the tps. Community work involving farmers and at the time of the election took place, in Blora district was harvesting so that farmers preferred to harvest their crops. Community political organizations strongly oppose political education because in political, social and other community organizations organizations are supporters of individual or group quality. Community members who are experienced in organization certainly have good political education.